Avaliação da Geometria e condições de operação de uma cabine aerosol box para intubação orotraqueal utilizando fluidodinâmica computacional - Boni, Bruno de (Universidade Federal de São Carlos, 2020)
On March 11, 2020, the World Health Organization declared a state of global Coronavirus pandemic. Today, Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2) and Coronavirus Disease 2019 (Covid-19) are considered the greatest worldwide threats to public health. With the need to provide greater protection to health professionals, who are daily exposed to high viral loads, the geometry and operating conditions of an aerosol box for orotracheal intubation, a procedure that presents a high risk of contamination for the medical team, are evaluated using fluid dynamics. The aerosol box, which is positioned over the patient's head, consists of a box of transparent material with attached suction, which serves as a barrier against the virus that can be transmitted by droplets of saliva and aerosols from the breath. The objective of this work was to computationally simulate, by the software ANSYS Student R2 2020, the fluid dynamics of an aerosol box under development at the Federal University of São Carlos, comparing eight cases with different configurations, such as: air flow rate in the patient's mouth, suction system flow rate, air flow rate on the arm orifices and number of suction pumps. Speed and pressure contour maps, velocity vector maps and pathlines maps obtained from the simulation were evaluated. The results indicated that the presence of suction pumps for suction of internal air prevented the leakage of contaminated air through the openings of the arm orifices and the lower opening, regardless of the presence of one or three suction pumps and sealing in the arms. The negative pressure caused by suction in the cabin was low, indicating that there would be no risk to the patient. In the absence of suction in the cabin, it is necessary to seal the arm orifices for greater protection of the medical team. Regarding the flow of air, the presence of three suction pumps was the most effective condition both for the flow dynamics and for the ability to drag particles; followed by the presence of one suction pump and, lastly, the condition of no suction pump was the most ineffective. The results indicated that the aerosol boxes have great potential for hospital application. The study of the fluid dynamics of aerosol boxes is current and necessary, bringing contributions to the theoretical understanding of this equipment and highlighting the main characteristics necessary to increase its safety.
Evaluation of Geometry and operating conditions of an aerosol box cabin for orotracheal intubation using computational fluid dynamics
Keywords: Intubação orotraqueal; Cabine; Fluidodinâmica computacional; CFD; ENGENHARIAS::ENGENHARIA QUIMICA